Pour une approche intégrative de la conduite délinquante des adolescents - LeBlanc, Marc (Criminologie, 1986)
During the I960's, the founders of criminology wanted to have it recognized as an autonomous discipline, not only because of its subject matter, but above all by assigning it an integrative mission. In this article, we propose to take this kind of integrative approach vis-à-vis the delinquent behaviour of adolescents. Based on a precise knowledge of the major forms of delinquent conduct, we formulate and validate a multidisciplinary theory of its emergence and development. With the aid of a typology of the delinquent, we then focus our attention on the practical implications of this knowledge of the subject and of the discovery of the mechanisms of its etiology. In this way, criminology can be shown to be both a science and multidisciplinary profession, hence integrative.